2012
DOI: 10.1186/1755-7682-5-23
|View full text |Cite
|
Sign up to set email alerts
|

Latent Autoimmune Diabetes Mellitus in Adults (LADA) and it’s characteristics in a subset of Nigerians initially managed for type 2 diabetes

Abstract: IntroductionLatent autoimmune diabetes in adults (LADA) is an entity characterized by the presence of GAD autoantibodies. LADA is largely understudied and underreported amongst Nigerians with Diabetes Mellitus (DM). We undertook to document the Prevalence, clinical and biochemical characteristics of LADA in a subset of Nigerians who hitherto had been treated for type 2 DM.MethodsThis is a cross-sectional study conducted on 235 patients being managed for type 2 DM. The diagnosis of LADA was made in the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
24
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 35 publications
11
24
1
Order By: Relevance
“…As a result, the misuse of SGLT2 inhibitors in autoimmune diabetes can pose a high risk to develop euDKA, as the present case illustrated. Interestingly, our case had severe metabolic acidosis (pH 6.972 and HCO3 1.5 mmol/L) along with borderline hyperglycemia (blood glucose 242 mg/dL) [12][13][14][15]. These extremely discordant data had not been reported in patients with T1DM yet.…”
Section: Case Reportmentioning
confidence: 54%
“…As a result, the misuse of SGLT2 inhibitors in autoimmune diabetes can pose a high risk to develop euDKA, as the present case illustrated. Interestingly, our case had severe metabolic acidosis (pH 6.972 and HCO3 1.5 mmol/L) along with borderline hyperglycemia (blood glucose 242 mg/dL) [12][13][14][15]. These extremely discordant data had not been reported in patients with T1DM yet.…”
Section: Case Reportmentioning
confidence: 54%
“…[9] among Indian population; however, previous studies in Southwest Nigeria reported no gender bias of GAD-Ab + among T2DM patients. [1415] The observed differences of GAD-Ab among gender between the current study (Northern Nigeria) and the previous (Southern Nigeria) may be due to population demographics and/or genetic predisposition. [24]…”
Section: Discussionmentioning
confidence: 83%
“…Different data reported from Africa, where the prevalence range 14%in Nigeria to 13.5% in Ghana to 7.3% in Tanzania [22][23][24].…”
Section: Discussionmentioning
confidence: 99%